2008
DOI: 10.1160/th07-06-0395
|View full text |Cite
|
Sign up to set email alerts
|

PAI-1 gene 4G/5G polymorphism, cytokine levels and their relations with metabolic parameters in obese children

Abstract: Obesity is associated with the changes of plasminogen activator inhibitor-1 (PAI-1), tumor necrosis factor-alpha (TNFalpha) and transforming growth factor beta (TGFbeta) levels. However, the precise effect of the 4G allele on obesity is still contradictory. Here, we aimed to elucidate the role of the 4G/5G polymorphism of the PAI-1 gene on the PAI-1 level and determine the associations between cytokines, glucose and lipid metabolism parameters in obese children. Thirty-nine obese children (mean age 11.4 +/- 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 24 publications
0
4
2
Order By: Relevance
“…While some case-control studies found differences in genotype distribution between obese and non-obese participants [45], [46], others did not [38]. Our data, providing the first population-based evidence, indicated that there were no differences in genotype distribution between individuals of normal weight and those who were overweight/obese.…”
Section: Discussioncontrasting
confidence: 55%
“…While some case-control studies found differences in genotype distribution between obese and non-obese participants [45], [46], others did not [38]. Our data, providing the first population-based evidence, indicated that there were no differences in genotype distribution between individuals of normal weight and those who were overweight/obese.…”
Section: Discussioncontrasting
confidence: 55%
“…In Children with obesity, Estelles et al [39] observed no influence of the 4 G/5 G polymorphism on PAI-1 levels. Moreover, no influence of the PAI-1 4 G/5 G polymorphism on lipid and glucose metabolism parameters was observed in Turkish obese children [40,41]. …”
Section: Discussionmentioning
confidence: 99%
“…[32] On the other hand, Yener et al showed lower levels of TGF-β in obese children without being correlated with lipid or insulin resistance, [33] while another study was also pointing out an indirect proportional relation between serum TGF-β levels, BMI, and waist circumference, respectively. [34] Wong et al [35] proved that the TGF-β1 869T > C (Leu10Pro) gene polymorphism is associated with type 2 diabetes mellitus, pointing out a correlation between the C allele of the TGF-β1 869T > C gene polymorphism and serum TGF-β levels.…”
Section: Introductionmentioning
confidence: 99%